Information literacy research of technical and vocational education and training in China in the past 10 years: a systematic literature review - Dai, Jiali; Jambari, Hanifah; Noh, Nur Hazirah; Hisham, Mohd Hizwan Mohd (Frontiers in Education, 2024)
Social and economic systematic changes create a new pattern of industrial structure and profession; technical and vocational education and training (TVET) is deeply connected to industrial upgrading and digital transformation because of its high relevance to cultivate emerging professional talents. Information literacy inevitably becomes the prevailing condition of sustainable development of TVET. Through a literature study, this systematic review selected and studied 61 journal articles related to information literacy in the TVET context in China from Web of Science (WOS) databases and China National Knowledge Infrastructure (CNKI) between 2014 and 2023. The main findings include; (a) technological, social and educational circumstances influence which receive extensive attention from researchers, (b) frequent use of narrative inquiry method with lack of empirical studies, (c) themes identified of information literacy among TVET institutions in China shows significant differences as compared to the themes of information literacy in higher education, and the reasons underlying this finding has been critically analysed. This review may interest academics, decision-makers and trainers in improving information literacy education among TVET institutions in China in line with the sophisticated demands of the industry and community.